Synergizing Social Welfare And Family Planning: A Policy Analysis Of Surabaya City’s Population Strategy - valenciadivaayu_stefannyputri (POLTRANS: Journal of Politics and Social Transformation, 2025)
This study analyses the synergy between social welfare policies and family planning programs as part of the Surabaya City Government’s strategy to control population growth. The research aims to examine how the integration of social assistance with Family Planning (FP) services contributes to sustainable population management and to evaluate the effectiveness of these policies through the lens of public policy theory by Merilee S. Grindle. Using a qualitative descriptive approach, data were collected through in depth interviews with government officials from the office of Women Empowerment, Child Protection, Population and Family Planning (DP3APPKB), as well as from documentation and literature review. The findings reveal that the linkage between social welfare programs and active participation in FP initiatives, supported by adequate budget allocation, inter-institutional cooperation, and accessible services, significantly increases community participation, including among men. Communication strategies, such as the slogan “Two Children Are Healthier” and community-based education through Family Development Groups, have effectively strengthened public awareness of reproductive health and population control. The study concludes that adaptive, integrated, and community-based policy implementation plays a crucial role in achieving population control goals. The synergy between social and population policies not only reduces the Total Fertility Rate (TFR) but also enhances the quality of life and social equity in urban communities.